To Compare the Mean Peak Flow Rate of Holmium Laser Versus Cold Knife Among Patients Undergoing Direct Visual Internal Urethrotomy - Muhammad Ibrahim Shaikh, Waqas Ahmed Memon, Raj Kumar, Zubda Malik, Ali Raza, Sana Khurshid (Pakistan Journal of Medical & Health Sciences, 2023)
Background: During the last two decades, laser methods have become popular among many people. The current study explores the differences in peak flows between holmium laser and cold knife during DVIU so as to maximize on the outcomes of this treatment modality in urethral strictures. Methodology: A prospective randomized controlled trial was carried out at the Department of Urology, Liaquat National Hospital in Karachi from January 1st, 2019, to June 30th, 2019. The study enrolled 130 patients, evenly divided into two groups: The patients of Group A were opened up using a cold knife method, and Group B was done using holmium laser. After the procedure, on the 30th day, the peak flow rate comparison between the two groups was conducted by an independent t-test, with a significance level set at p ≤ 0. 1. 05. The experimental configuration and quantitative analysis approach thus formed a reliable basis for investigating the activity of the two different treatment modalities for the urethral stricture. Results: The pre-operative mean peak flow rate was recorded as 6. 32±1. 27 ml/s in group-A and 7.3c6±1.37 ml/s in group-B. The average peak flow rate on the 3rd day was 26.66±3.69 ml/s in group-A and 28.72±4.63 ml/s in group-B. The peak flow rate on the 30th day is 24. 00±3. 44 ml/s in groups A and 20.84±2.77 ml/s in group B. The results indicated a significant mean difference for the mean peak flow rate on the 30th day according to study groups (p-value=0. 000). Conclusion: Both knives and lasers have proved to be effective therapeutic modalities in delivering prompt relief to patients with urethral strictures. However, it was noted that those who underwent the procedure with a cold knife produced better long-term results. Keywords: Mean Peak Flow Rate, Holmium Laser, Cold Knife, Direct Visual Internal Urethrotomy